Pemerolehan Bahasa Arab sebagai Bahasa Kedua (Kajian Psikolinguistik) - Annisa, Maryam Nur; Arista, Dian; La Udin, Yadin; Wargadinata, Wildana (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
Acquiring Arabic as a second language is a complex process influenced by various factors. In this literature review, we explore the factors that affect the acquisition of Arabic as a second language from a psycholinguistic perspective. We highlight three main factors, namely motivation, language factors, and social factors. Strong and sustained motivation plays a crucial role in motivating learners to diligently and consistently learn Arabic. A good understanding of the differences between the first language and Arabic is also found to be a significant factor, as this understanding helps learners overcome difficulties and develop a better grasp of the Arabic language. Additionally, social factors, such as interaction with native speakers and a supportive learning environment, provide valuable opportunities for learners to actively practice Arabic. This research has important implications for understanding Arabic as a second language. By understanding the factors that influence the acquisition of Arabic, more effective learning approaches can be developed. We provide suggestions to enhance learner motivation, consider first language factors in language learning, encourage social interaction, and integrate cultural contexts into Arabic language learning. The relevance of this research lies in its contribution to our understanding of the acquisition of Arabic as a second language and providing guidance to educators and learners in developing optimal learning strategies. Thus, it is expected that this article will provide valuable insights and contribute to the field of Arabic language acquisition as a second language from a psycholinguistic perspective.